COGNITIVE DISSONANCE IN THE IMPOLITE UTTERANCES OF FATHERLESS WOMAN - Rizky Ananda; Sri Minda Murni; Winda Setia Sari (RADJA PUBLIKA, 2025)
Fatherless women often experience unresolved emotional trauma and inner conflict that can surface in their speech. This study examines how impolite language used by five Indonesian women (aged 18–30) who grew up without fathers reflects underlying cognitive dissonance and emotional regulation strategies. Chat transcripts and interview data were analyzed using Culpeper’s impoliteness framework and Festinger’s theory of dissonance. The women’s utterances were categorized by type and function, revealing that 33% were direct, “bald-on-record” insults (e.g., “Bajingan kali jadi orang tua” (“What a bastard of a parent”)), while positive impoliteness and sarcasm each accounted for 24%, and negative impoliteness 19%. Nearly half of all impolite utterances served to express pent-up anger or disappointment, 32% served to assert dominance over the absent father, and 20% to signal identity (e.g. rejecting the obedient daughter role). These hostile expressions were immediately followed by internal conflict: participants felt torn between cultural norms (respectful daughter) and their cathartic outburst. Consistent with Festinger’s (1957) model, the most common dissonance-reduction strategy was reframing the behavior (justification) (36%), such as insisting “I know it’s rude, but it’s the fastest way to show I’m disappointed”. Other strategies included behavioral change (24%), avoiding conflict (20%), and environmental adjustment (20%). These findings suggest that impolite utterances in this context are not random aggression but purposeful emotional outlet and coping mechanisms. The women use language both to release long-suppressed trauma and to negotiate their sense of self, later employing cognitive strategies to restore consonance with their internal values. This complex interplay of linguistic expression and psychological regulation underscores impoliteness as a form of self-protective agency rather than mere rudeness.